Microbiological analysis of water and thickeners used for people with dysphagia. (1st April 2020) - Boaden, Elizabeth; Thomas, Lois; Higham, Susan; Watkins, Caroline
Abstract : Background: Thickened fluids are a recognised intervention strategy in use for people with dysphagia. However, their bacterial profile has not previously been examined. Aims: To identify bacteria and changes in bacterial profiles in a range of water sources and thickener preparations over a 5-day period. Methods: Nine experiments were performed using a range of preparations of water (sterile, drinking, non-drinking tap water) and a thickening agent (sterile sachet and a used tin). Findings: No bacteria were grown on serial subcultures of sterile water, both with and without thickener. Drinking, tap and thickened water left at room temperature for 24 hours may become contaminated with environmental organisms. Conclusions: The growth of bacteria in preparations of thickening agent appears to be dependent upon water quality, while the proliferation of bacteria is dependent upon the length of time the preparation is allowed to stand at room temperature.